Production of offspring from vacuum-dried mouse spermatozoa and assessing the effect of drying conditions on sperm DNA and embryo development - Natsuki USHIGOME; Sayaka WAKAYAMA; Kango YAMAJI; Daiyu ITO; Masatoshi OOGA; Teruhiko WAKAYAMA (The Society for Reproduction and Development, 2022)
Freeze-dried sperm (FD sperm) are of great value because they can be stored at room temperature for long periods of time, However, the birth rate of offspring derived from FD sperm is low and the step in the freeze-drying process particularly responsible for low offspring production remains unknown. In this study, we determined whether the drying process was responsible for the low success rate of offspring by producing vacuum-dried sperm (VD sperm), using mouse spermatozoa dried in a vacuum without being frozen. Transfer of embryos fertilized with VD sperm to recipients resulted in the production of several successful offspring. However, the success rate was slightly lower than that of FD sperm. The volume, temperature, and viscosity of the medium were optimized to improve the birth rate. The results obtained from a comet assay indicated that decreasing the drying rate reduced the extent of DNA damage in VD sperm. Furthermore, even though the rate of blastocyst formation increased upon fertilization with VD sperm, full-term development was not improved. Analysis of chromosomal damage at the two-cell stage through an abnormal chromosome segregation (ACS) assay revealed that reduction in the drying rate failed to prevent chromosomal damage. These results indicate that the lower birth rate of offspring from FD sperm may result from the drying process rather than the freezing process.